Fabrication of an induction coil magnetometer for geomagnetic field measurement (2010)
The measurement of magnetic variations within the low frequency range of 0.1 to 40Hz requires a highly sensitive magnetometer. A magnetometer based on the induction coil principle was designed, simulated, and constructed in this research. The search coil was designed by winding 4,500 turns of insulated coil on PVC pipe with 3 silicon-iron strips mounted on the PVC for higher magnetic susceptibility. The sensory method of the coil is based on the faraday’s law of electromagnetic induction. The output of the coil was amplified and filtered with a band pass electronic system designed to pass the desired frequency range of 0.1 to 40Hz. A simple calibration system using the Helmoltz coil pair was designed for the calibration of the sensor to determine the conversion factor of the output root mean square (r.m.s.) voltage with the external magnetic field (Hs), since the Helmoltz coil can generate very uniform magnetic field up to 25% or more of the covered area from the centre axis. The output voltage and applied magnetic field obtained as the calibration data were fitted into a linear graph. A relatively high sensitivity of 299mv/pT was obtained.